The use of a three-dimensional mesh in plastic surgery - Rodrigo de Faria Valle Dornelles; Nivaldo Alonso; Luiz Alexandre Lorico Tissiani; Anderson Rodrigo Souza; Lúcia Nocchi Cardim (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: Image recording as we know it today has evolved considerably from the beginning of photography by means of light printing directly onto a photosensitive material, up to the mathematical algorithms that constitute three-dimensional (3-D) meshes in stereophotogrammetry. The 3-D technology to capture and extract reliable information in plastic surgery has evolved considerably in recent years. However, the procedure for which the applicability potential can be exploited directly by the surgeon in their routine work should be fully understood. The objective of this work was to address the conceptual aspects and the accuracy of the image capture, and to illustrate clinical applications of 3-D meshes, with emphasis on their importance in clinical use. METHODS: Literature on the principles of image capture and formation of tridimensional models was reviewed, as well as the description of the application of the tests of accuracy with the use of a structured-light scanner. Clinical indications of 3-D meshes were evaluated both in the preoperative planning and postsurgical follow-up. RESULTS: The principles of the image capture technologies were established, and the reproducibility of the validation of the tool to capture meshes was confirmed. The clinical applicability both in programming and monitoring was exemplified. CONCLUSION: The conceptual difference between photography and the 3-D mesh system was established, together with the introduction of the principles of 3-D technology. The clinical applications of the method were presented, evidencing the promising application of dimensional models in plastic surgery.